WADAH PERTUKARAN PENGALAMAN RUANG DI MENTENG - Muhammad Yumna Helmy; Fermanto Lianto (Jurusan Arsitektur dan Perencanaan, 2020)
The urban life is not separated from the saturation of the daily routine and activities, which causes the level of stress ratio in major cities such as Jakarta is quite high. During the demands and routine of life, many people looking for entertainment or recreation to take off the fatigue of daily activities. The role of interaction room for the people of Menteng is very important, in addition to the physical layout of the environment, the public space also bears the function and significance of social and cultural very high. However, the rapid growth of the city's demand for urban land demands increased. The privatization of land, either individually, as well as legal entities/institutions, has caused the existence of public space to be increasingly affected. Even in the crowded settlements of residents, people have no more public space adequate to host their activities. People no longer have a shared space to interact with each other, communication between citizens; children no longer have a place to play in the outside space, so that the culture of togetherness and tolerance is increasingly misguided. With the presence of this container during busy and the needs of the surrounding community, it is expected to increase the attitude of tolerance between the community and produce new activities that can increase the productivity and tolerance between the surrounding residents who have a wide impact on the region. Abstrak Kejenuhan akan rutinitas serta aktivitas harian yang serba padat mwarnai kehidupan di perkotaan, hal ini yang mengakibatkan tingkat rasio kemungkinan stress di kota-kota besar seperti Jakarta lumayan besar. Ditengah rutinitas hidup, banyak orang yang mencari hiburan maupun rekreasi untuk semata-mata melepas kepenatan dari aktivitas sehari-hari. Kedudukan ruang interaksi bagi warga Menteng sangat berarti, tidak hanya menyangkut tata ruang fisik lingkungan, ruang publik juga mengemban peranan dan arti sosial serta kultural yang sangat besar. Tetapi, perkembangan kota yang cepat mengakibatkan tuntutan kebutuhan lahan perkotaan kian bertambah. Privatisasi lahan baik secara individual ataupun badan hukum/lembaga telah menimbulkan eksistensi ruang publik kian terpinggirkan. Apalagi di permukiman-permukiman padat penghuni, warga sudah tidak mempunyai lagi ruang publik yang mencukupi untuk mewadahi aktivitas mereka. Penduduk tidak lagi mempunyai ruang bersama buat silih korelasi, komunikasi antar warga, anak-anak tidak lagi mempunyai tempat bermain yang nyaman di ruang luar, sehingga budaya kebersamaan serta toleransi terus menjadi terkikis. Dengan hadirnya wadah ini di tengah tengah kesibukan dan kebutuhan masyarakat sekitar, diharapkan dapat meningkatkan sikap toleransi antar masyarkat dan menghasilkan kegiatan kegiatan yang baru yang dapat meningkatkan produktivitas dan toleransi antar warga sekitar yang berdampak luas terhadap kawasan sekitar.